Single-step fabrication of Ag2S/poly-2-mercaptoaniline nanoribbon photocathodes for green hydrogen generation from artificial and natural red-sea water - Aldosari Eman; Rabia Mohamed; Sanna Aimaro; Farid Osama (Open Physics)
A novel and highly promising Ag2S-P2MA nanoribbon photocathodes are synthesized using a single-step technique based on 2-mercaptoaniline oxidation with (NH4)2S2O8 and AgNO3. This process yields polymer composites with nanoribbon morphologies, typically 150 nm wide and ranging from 500 to 1,000 nm in length. These nanoribbons exhibit excellent absorbance across the entire optical spectrum up to 780 nm. The fabricated Ag2S/P2MA photocathode is designed for water splitting to generate hydrogen gas using two different electrolytes: natural Red Sea water and artificial seawater free from heavy metals. This variation allows observation of the impact of seawater’s heavy metals. Hydrogen gas production is studied using a three-electrode cell with linear sweep voltammetry at room temperature. In both electrolytes, the photocurrent is measured at 0.015 mA/cm2. However, both the current density in light (J ph) and dark (J o) values decrease in artificial seawater compared to natural seawater, with values of −0.033 and −0.017 mA/cm2 in natural seawater and −0.027 and −0.012 mA/cm2 in artificial seawater. The Ag2S-P2MA nanoribbon photocathodes exhibit stable behavior, producing hydrogen at a rate of 12 µmol/cm2 h. Combined with their cost-effectiveness and potential for mass production, this positions them as viable candidates for commercial electrode applications in various industrial settings.